Nasopalatine Duct Cyst with Impacted Inverted Mesiodens: A Rare Case Report and Literature Review - Shamimul Hasan; Deepika Bablani Popli; Syed Ansar Ahmad; Keya Sircar; Shahnaz Mansoori; Kirti Dua (Case Reports in Dentistry)
Nasopalatine duct cyst (NPDC) is a non-odontogenic, developmental epithelial cyst that accounts for 1% of maxillary cysts. It often arises due to the spontaneous proliferation of the epithelial tissue remnants, although trauma, bacterial infection, and mucous retention may also trigger the proliferation. Owing to its slow-growing, asymptomatic nature, the cyst is often discovered as an accidental finding during routine clinical and radiographic examinations. However, the majority of cases present as a tiny, asymptomatic swelling just posterior to the palatine papillae. Radiographically, it appears as a well-defined oval or round radiolucency in the maxillary anterior teeth region and should be differentially diagnosed with inflammatory periapical lesions and a wide incisive foramen. A pulp vitality test is essential to rule out lesions of endodontic origin. Microscopically, NPDCs display a mixed pattern of the epithelial lining and exhibit neurovascular bundles (small to medium-sized nerves, arteries, and veins), and minor salivary glands in the cystic connective tissue, a distinctive feature facilitating a confirmatory diagnosis. Enucleation and marsupialization remain the treatment of choice. NPDC associated with impacted mesiodens is an extremely uncommon entity. A comprehensive literature search carried out on the PubMed and Google Scholar search engines revealed only three cases of NPDC with impacted mesiodens to date. The purpose of this study is to report an extremely rare case of NPDC associated with an impacted inverted mesiodens in a 19-year-old male patient who presented with an asymptomatic swelling in the maxillary anterior teeth region. To the best of our knowledge, this is only the fourth reported case of NPDC with impacted mesiodens.